Subprime crisis and board (in-)competence : private vs. public banks in Germany - Harald Hau; Marcel Thum (Center for Economic Studies and ifo Institute (CESifo), 2009)
We examine evidence for a systematic underperformance of Germany's state-owned banks in the current financial crisis and study if the bank losses can be traced to the quality of bank governance. For this purpose, we examine the biographical background of 593 supervisory board members in the 29 largest banks and find a pronounced difference in the finance and management experience of board representatives across private and state-owned banks. Measures of boardroom competence are then related directly to the magnitude of bank losses in the recent financial crisis. Our data confirms that supervisory board (in-)competence in finance is related to losses in the financial crisis. Improved bank governance is therefore a suitable policy objective to reduce bank fragility.
Keywords: G2; G21; G3; G32; 330; governance; supervisory boards; banking; financial crisis; Bankmanagement; Aufsichtsrat; Kompetenz; Corporate Governance; Vergleich; Bankinsolvenz; Öffentliche Bank; Subprime-Hypothek; Bankenkrise; Finanzmarktkrise; Deutschland